Effect of concentration veriations exstract etanol salam leaves (eugenia polyantha wight) on risk free radicals dpph (1,1-diphenyl-2-picrylhydrazyl) - Guntarti, Any; Nurdiansyah, Nurdiansyah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Background: Salam leaves (Eugenia polyantha Wight) contains antioxidant compounds, flavonoids and polyphenols. These compounds are reported to inhibit oxidation activity by binding with free radicals. The unlimited amount of free radicals in the body will increase the risk of contracting degenerative diseases. Objective: The purpose of this study was to identify compounds from the ethanol extract of salam leaves and to test the antioxidant activity of its compounds using DPPH method and also determine the IC50 (Inhibition Concentration 50) of between the ethanol extract of salam leaves and quercetin standard. Methods: Ethanol concentration extract of salam leaves were obtained by maceration method with the ethanol solution. The compounds were identified by phytochemical screening. The concentration used for the extraction of salam leaves were 30%, 40% and 50%. The variations of each extract concentration were 50, 75, 100, 125 and 150 mg/mL. The variations of standard quercetin concentration were 1, 2, 3, 4 and 5 mg/mL. Antioxidant activity was tested by visible spectrophotometry using the DPPH method. The antioxidant activity is represented as the per cent of free radical scavenging and IC50. Results: The 30%, 40% and 50% ethanol extract of salam leaves contained flavonoid and polyphenol compounds, and also had free radical binding activity. The average value of IC50 quercetin, 30%, 40% and 50% ethanolic extract of salam leaves were 1.68, 102.48, 149.88 and 197.19 mg/mL. Conclusion: Statistical analysis showed that the antioxidant activity between quercetin, 30%, 40% and 50% ethanol extract of salam leaves were significantly different (P=95%).